People's trust: the design of a survey-based experiment - John Ermisch; Diego Gambetta (University of Essex, Institute for Social and Economic Research (ISER), 2006)
In this paper we present the design of a two-stage experiment which aims to measure trusting and trustworthiness in a representative sample of the British population. In the first part we discuss the shortcomings of the most common design of the trust-game experiment in eliciting information about clear and cogent notions of trusting and trustworthiness, and in the second part we present an alternative design, which we call the framed binary trust game. The basic design will be administered to a sample of 200 subjects who were formerly members of the British Household Panel Survey (BHPS). In the third part of the paper, we extend this design to allow the truster to purchase some information about the trustee so as to make the experiment a better representation of real-life trust decisions. We plan in a second stage to run the extended experiment on a larger sample of about 1000 subjects.
Keywords: 330